Mammakarzinom in der Schwangerschaft - Seitz, Julia; Au, Alexandra von; Sohn, Christof; Marmé, Frederik; Schneeweiss, Andreas (Der Onkologe, 2018)
Background and objective: Breast cancer during pregnancy is rare. Nonetheless, its incidence is on the rise which is certainly associated with the increasing age of women at the time of conception. The likelihood for detection of advanced stages of breast cancer with unfavorable tumor biology is higher. This is partially due to the more difficult and thus delayed diagnostics. Therefore, a multimodal approach and treatment is required. The best possible treatment for mother and child frequently remains uncertain. Results and conclusion: This review article highlights the diagnostic, local and systemic treatment options for breast cancer during pregnancy. In summary it could be shown that there are safe medicinal and surgical options, which can be administered after the first trimester. The prognosis for the mother and development of the child are not affected by breast cancer and its treatment. The diagnosis of pregnancy associated breast cancer does not rnecessarily represent indications for the termination of pregnancy.
Gesehen am 27.09.2019